The BioSat indices designed for biodiversity science and conservation - Volker C. Radeloff; Eduarda M.O. Silveira; Akash Anand; Duanyang Liu; Kathleen A. Carroll; Nicholas C. Coops; Gabriel C. Costa; Maxim Dubinin; Laura S. Farwell; Paul R. Elsen; Martina L. Hobi; Elena Razenkova; et al. (Remote Sensing of Environment, 2026)

Structural characterization, in vitro anticoagulant, and antiplatelet activities of a Distolasterias nipon dermatan sulfate-like polymer with a distinctive sulfation pattern - Alina P. Filshtein; Vlada S. Belova; Ilya V. Taran; Maxim S. Kokoulin (Carbohydrate Polymers, 2026)

The rodZ repeat region of Erwinia amylovora: genetic diversity and possible functional implications - Nataliya V. Drenova; Alexandr N. Ignatov; Fabio Rezzonico; Galina N. Bondarenko; Denis L. Belkin; Maxim O. Kondratyev; Fevzi S-U. Dzhalilov; Theo H. M. Smits (Journal of Plant Pathology, 2026)

Remote photothermal actuation of enzymes: A sol-gel strategy for plasmon-enhanced and stabilized biocatalysis - Pavel Sazonov; Nikita Chernov; Andrey S. Drozdov; Maxim P. Nikitin (Chemical Engineering Journal, 2026)

Alien Chinese pond mussels (Unionidae, Sinanodonta) in Russia: new records, the stages of the invasion, and its current status - Evgeniy S. Babushkin; Maxim V. Vinarski; Ilya V. Vikhrev; Ivan N. Bolotov; Alexander V. Kondakov; Mikhail Yu. Gofarov; Liubov V. Yanygina; Dmitry V. Kuzmenkin (Hydrobiologia, 2026)

Noctilucent clouds modulated by strong 5-day planetary wave in 2025: amplitudes, phases and altitudes based on ground-based observations and satellite temperature data - Oleg S. Ugolnikov; Ilya S. Yankovsky; Nikolay N. Pertsev; Vladimir I. Perminov; Maxim V. Klimenko; Ekaterina N. Tipikina; Alexey V. Popov; Andrey M. Tatarnikov; Sergey G. Zheltoukhov; Sergey A. Potanin; Egor O. Ugolnikov; Olga Yu. Golubeva; et al. (Advances in Space Research, 2026)

Melting flows: Russian climate change science in the global research landscape - Alexey M. Zheleznov; Ekaterina L. Dyachenko; Maxim Y. Dmitriev; Katerina S. Guba (Climatic Change, 2026)

Novelties in Vietnamese Psychotria (Rubiaceae): P. magnifructa, a new species, P. monticola, a new national record, and notes on P. balansae - Quoc Bao Nguyen; Quang Diep Dinh; Van Son Dang; Shuichiro Tagane; Ba Vuong Truong; Van Toan Em Quach; Van Huong Bui; Hong Quang Bui; Duc Binh Tran; Maxim S. Nuraliev; Alexander N. Sennikov; Tuan Anh Le; et al. (Brittonia, 2026)

Biodegradation of cellophane in the digestive tracts of echinoderms and gastropods - Vyacheslav S. Odintsov; Alexander A. Karpenko; Aleksandra A. Istomina; Maxim A. Karpenko (Environmental Science and Pollution Research, 2026)

Evaluating snow leopard population connectivity: is Kazakhstan a bridge for gene flow between the northern and southwestern range? - Miroslav P. Korablev; Alexey A. Grachev; Andrey D. Poyarkov; Saltore K. Saparbayev; Jose A. Hernandez-Blanco; Sergey V. Bespalov; Maxim V. Bespalov; Yerlik R. Baidavletov; Dmitry Yu. Alexandrov; Alexander S. Karnaukhov; Sergey V. Malykh; Bariushaa Munkhtsog; et al. (Mammalian Biology, 2026)

Species richness of Enchytraeidae (Enchytraeidae: Clitellata: Annelida) in the center and east of northern Palaearctic - Andrey S. Zaitsev; Maxim I. Degtyarev; Daniil I. Korobushkin; Ruslan A. Saifutdinov; Margarita A. Danilova; Dmitriy A. Medvedev; Elena Yu. Zvychaynaya; Konstantin B. Gongalsky (Applied Soil Ecology, 2026)

Electromagnetic phenomena associated with dust particle dynamics in a simulated Martian atmosphere: an experimental study - Mohamad E. Abdelaal; Maxim A. Zaitsev; Egor M. Sorokin; Inna.A. Shashkova; Anna S. Kuzovchikova; Elena I. Seran; Alexander V. Zakharov (Advances in Space Research, 2026)

Global Molecular Taxonomy, Phylogeny and Biogeography of the Clam Genus Corbicula (Bivalvia: Cyrenidae) - Yulia V. Bespalaya; Alexander V. Kropotin; Olga V. Aksenova; Mikhail Yu. Gofarov; Alexander V. Kondakov; Ekaterina S. Konopleva; Irina S. Khrebtova; Youness Mabrouki; Dmitry M. Palatov; Alexander A. Prokin; Dmitry P. Karabanov; Oksana V. Travina; et al. (Zoologica Scripta, 2026)
The Corbicula clams (Bivalvia: Cyrenidae) are an ecologically significant and widespread group of fresh‐ and brackish‐water molluscs, playing a keystone role in aquatic ecosystems. Some species of this genus are subglobal invaders. The taxonomy of Corbicula remains very confusing, which hinders both fundamental and applied research on this genus. A comprehensive revision of the taxonomic structure of this group has been lacking so far. In this paper, we clarify the taxonomy, distribution, and evolutionary biogeography of the living representatives of the genus Corbicula , including species widely distributed in their non‐native ranges, on the basis of the largest dataset of DNA sequences ever analysed. Our data reveal that the genus Corbicula contains two subgenus‐level clades: Corbicula s.s. and Sphaerocorbicula Bolotov, Bespalaya & Aksenova subgen. nov. Our COI mtDNA and two‐locus phylogenies reveal that the genus Corbicula contains not Corbicula bilini Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Bilin River, Myanmar) and C. lemroae Bespalaya, Kropotin, Kondakov, Konopleva & Bolotov sp. nov. (Lemro River, Myanmar). A new synonymy is established for five species of Corbicula and one is transferred from the family Sphaeriidae to Cyrenidae. Our fossil‐calibrated phylogeny and generalised biogeographic model indicate that the most recent common ancestor of the genus Corbicula could have originated somewhere within a broad area covering Asia near the upper boundary of the Middle Cretaceous.

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

The rare plioplatecarpine mosasaur Latoplatecarpus in Europe as further evidence of a semi-global Campanian marine vertebrate fauna - Dmitry V. Grigoriev; Maxim S. Arkhangelsky; Nikolay G. Zverkov; Denis I. Gubarev (Cretaceous Research, 2025)

Physical Interpretation of Interwell Partitioning Tracer Tests for Estimation of Remaining Oil Saturation in Layered Carbonate Reservoirs - Samuel D. Fontalvo; Maxim P. Yutkin; S. Majid Hassanizadeh; Clayton J. Radke; Tadeusz W. Patzek (Transport in Porous Media, 2025)
Interwell partitioning tracer tests (IPTTs) are conducted in mature oil fields to estimate remaining oil in place, which is crucial for subsequent economic analyses and decisions regarding further field development. An IPTT involves the simultaneous injection of two types of tracers: conservative and partitioning, that probe the aqueous and oil phases, respectively. Although this test requires time, it probes the entire fluid flow path, not just the near-wellbore area, as is the case with other methods such as single-well tests. Accurate interpretation of interwell tracer test data is of critical importance for the oil and gas industry. Published IPTT case studies lack physical justification for the choice of tracer flow models. In this study, we provide such justifications along with guidelines for selecting appropriate tracer flow models. First, we review existing models for the transport of partitioning and conservative tracers and demonstrate their applicability range based on mass conservation analysis. Based on this analysis, we propose a refined model of partitioning tracer flow with Robin boundary conditions that accounts for non-equilibrium partitioning. Such analysis is missing in the literature. Next, we illustrate errors in estimating remaining oil if an inappropriate model is used for data interpretation. Notably, the choice of an incorrect model can lead to either underestimation or overestimation of the remaining oil, with the latter being of greater financial concern. Finally, we apply the non-equilibrium partitioning model to a published IPTT dataset from a layered carbonate reservoir and compare our remaining oil estimates with results of the original study. To the best of our knowledge, analysis of such cases with non-equilibrium partitioning has not been documented in the literature.

Study on the modifying effect of cobalt in Pd-Co/α-Al2O3 catalysts for ethylene production by acetylene hydrogenation - Daria V. Yurpalova; Zakhar S. Vinokurov; Igor P. Prosvirin; Maxim A. Panafidin; Andrey V. Bukhtiyarov; Mikhail V. Trenikhin; Evgeny Yu. Gerasimov; Tatyana I. Gulyaeva; Victor L. Temerev; Larisa M. Kovtunova; Vyacheslav L. Yurpalov (Chemical Engineering Journal, 2025)

On the Origin of Plant Tissues: Advantages and Limitations of Anatomy - Alexey V. F. Ch. Bobrov; Nikita S. Zdravchev; Alexey N. Sorokin; Mikhail S. Romanov; Jorge V. Crisci; Liliana Katinas; Petr S. Iovlev; Anton S. Timchenko; Anna A. Mikhaylova; Natalia D. Vasekha; Olga V. Yatsenko; Kirill V. Kuptsov; et al. (The Botanical Review, 2025)

Metabarcoding of a mock community of soil invertebrates: DNA extraction, false positives, and data filtration - Ivan V. Sotnikov; Maxim V. Vecherskii; Vladimir S. Cheptsov; Alexei V. Tiunov (Pedobiologia, 2025)

Combined irradiation by gamma-rays and carbon-12 nuclei caused hyperlocomotion and change in striatal metabolism of rats - Viktor S. Kokhan; Kirill Chaprov; Denis A. Abaimov; Maxim S. Nesterov; Vladimir A. Pikalov (Life Sciences in Space Research, 2025)

Capsular polysaccharide from the marine bacterium Cobetia marina induces apoptosis via both caspase-dependent and mitochondria-mediated pathways in HL-60 cells - Maxim S. Kokoulin; Alexandra S. Kuzmich; Alina P. Filshtein; Vladimir S. Prassolov; Lyudmila A. Romanenko (Carbohydrate Polymers, 2025)

Bottom-up designing nanostructured oxide libraries under a lab-on-chip paradigm towards a low-cost highly-selective E-nose - Maksim A. Solomatin; Fedor S. Fedorov; Demid A. Kirilenko; Vanessa Trouillet; Alexey S. Varezhnikov; Ilia V. Kiselev; Udo Geckle; Martin Sommer; Alexey M. Bainyashev; Vasily Artemov; Nikolay M. Ushakov; Vladimir G. Goffman; et al. (Analytica Chimica Acta, 2025)

Impact of global environmental changes on the range contraction of Eurasian moose since the Late Pleistocene - Magdalena Niedziałkowska; Marcin Górny; Joanna Gornia; Danijela Popović; Mateusz Baca; Urszula Ratajczak-Skrzatek; Oleksandr Kovalchuk; Maciej Sykut; Małgorzata Suska-Malawska; Paweł Mackiewicz; Emilia Hofman-Kamińska; Rafał Kowalczyk; et al. (Science of The Total Environment, 2024)

Uncovering the taste features: Applying machine learning and molecular docking approaches to predict umami taste intensity of peptides - Mariia S. Ashikhmina; Artemii M. Zenkin; Igor S. Pantiukhin; Igor G. Litvak; Pavel V. Nesterov; Kunal Dutta; Sergey Shityakov; Michael Nosonovsky; Maxim A. Korablev-Dyson; Olga Y. Orlova; Sviatlana A. Ulasevich; Ekaterina V. Skorb (Food Bioscience, 2024)

Structure and in vitro antiproliferative activity against breast cancer cells of the cell-wall polysaccharide from the marine bacterium Kangiella japonica KMM 3899T - Maxim S. Kokoulin; Alexandra S. Kuzmich; Lyudmila A. Romanenko (Carbohydrate Polymers, 2024)

Characterizing a lethal CAG-ACE2 transgenic mouse model for SARS-CoV-2 infection using Cas9-enhanced nanopore sequencing - Alexander Smirnov; Artem Nurislamov; Galina Koncevaya; Irina Serova; Evelyn Kabirova; Eduard Chuyko; Ekaterina Maltceva; Maxim Savoskin; Daniil Zadorozhny; Victor A. Svyatchenko; Elena V. Protopopova; Oleg S. Taranov; et al. (Transgenic Research, 2024)

Hydrogenation of calcite and change in chemical bonding at high pressure: Diamond formation above 100 GPa - Alexander F. Goncharov; Huiyao Kuang; John S. Tse; Eric Edmund; Maxim Bykov; Elena Bykova; Stella Chariton; Vitali B. Prakapenka; Timofey Fedotenko; Nico Giordano; Mohamed Mezouar; Jesse S. Smith (Physics of the Earth and Planetary Interiors, 2024)

Enhanced radiation hardness of lead halide perovskite absorber materials via incorporation of Dy2+ cations - Marina I. Ustinova; Lyubov A. Frolova; Alexandra V. Rasmetyeva; Nikita A. Emelianov; Maxim N. Sarychev; Pavel P. Kushch; Nadezhda N. Dremova; Galina A. Kichigina; Andrey I. Kukharenko; Dmitry P. Kiryukhin; Ernst Z. Kurmaev; Ivan S. Zhidkov; et al. (Chemical Engineering Journal, 2024)

Taxon-specific ability of saprophagous soil macrofauna to reintegrate carbon from agricultural waste into soil - Andrey S. Zaitsev; Anastasia Yu. Gorbunova; Alexander I. Bastrakov; Maxim I. Degtyarev; Donghui Wu; Daniil I. Korobushkin; Ruslan A. Saifutdinov; Konstantin B. Gongalsky (Pedobiologia, 2024)

Reaction of NaBH4 and NaB(OH)4 as a way to increase the yield of hydrogen in catalytic hydrolysis of sodium borohydride by water - Mikhail V. Solovev; Georgiy V. Malkov; Anastasiia A. Reveguk; Anastasiia O. Antonenko; Dmitriy I. Elets; Alexey S. Maystro; Pavel Yu. Buldakov; Yuriy A. Dobrovolsky; Alexey V. Shihovtsev; Maxim V. Tsvetkov; Oleg V. Kravchenko (Fuel, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Detection of two species of non-indigenous freshwater snails in Arctic Siberia - Ivan O. Nekhaev; Evgeniy S. Babushkin; Irina S. Khrebtova; Alexander V. Kondakov; Olga V. Aksenova; Maxim V. Vinarski (Molluscan Research, 2024)

Increasing outer membrane complexity: the case of the lipopolysaccharide lipid A from marine Cellulophaga pacifica - Emanuela Andretta; Stefania De Chiara; Chiara Pagliuca; Roberta Cirella; Elena Scaglione; Martina Di Rosario; Maxim S. Kokoulin; Olga I. Nedashkovskaya; Alba Silipo; Paola Salvatore; Antonio Molinaro; Flaviana Di Lorenzo (Glycoconjugate Journal, 2024)
Gram-negative bacteria living in marine waters have evolved peculiar adaptation strategies to deal with the numerous stress conditions that characterize aquatic environments. Among the multiple mechanisms for efficient adaptation, these bacteria typically exhibit chemical modifications in the structure of the lipopolysaccharide (LPS), which is a fundamental component of their outer membrane. In particular, the glycolipid anchor to the membrane of marine bacteria LPSs, i.e. the lipid A, frequently shows unusual chemical structures, which are reflected in equally singular immunological properties with potential applications as immune adjuvants or anti-sepsis drugs. In this work, we determined the chemical structure of the lipid A from Cellulophaga pacifica KMM 3664 T isolated from the Sea of Japan. This bacterium showed to produce a heterogeneous mixture of lipid A molecules that mainly display five acyl chains and carry a single phosphate and a D-mannose disaccharide on the glucosamine backbone. Furthermore, we proved that C. pacifica KMM 3664 T LPS acts as a weaker activator of Toll-like receptor 4 (TLR4) compared to the prototypical enterobacterial Salmonella typhimurium LPS. Our results are relevant to the future development of novel vaccine adjuvants and immunomodulators inspired by marine LPS chemistry.

CheekAge: a next-generation buccal epigenetic aging clock associated with lifestyle and health - Maxim N. Shokhirev; Nicole S. Torosin; Daniel J. Kramer; Adiv A. Johnson; Trinna L. Cuellar (GeroScience, 2024)
Epigenetic aging clocks are computational models that predict age using DNA methylation information. Initially, first-generation clocks were developed to make predictions using CpGs that change with age. Over time, next-generation clocks were created using CpGs that relate to both age and health. Since existing next-generation clocks were constructed in blood, we sought to develop a next-generation clock optimized for prediction in cheek swabs, which are non-invasive and easy to collect. To do this, we collected MethylationEPIC data as well as lifestyle and health information from 8045 diverse adults. Using a novel simulated annealing approach that allowed us to incorporate lifestyle and health factors into training as well as a combination of CpG filtering, CpG clustering, and clock ensembling, we constructed CheekAge, an epigenetic aging clock that has a strong correlation with age, displays high test–retest reproducibility across replicates, and significantly associates with a plethora of lifestyle and health factors, such as BMI, smoking status, and alcohol intake. We validated CheekAge in an internal dataset and multiple publicly available datasets, including samples from patients with progeria or meningioma. In addition to exploring the underlying biology of the data and clock, we provide a free online tool that allows users to mine our methylomic data and predict epigenetic age.

Sterically hindered phenolic derivatives: effect on the production of Pseudomonas aeruginosa virulence factors, high-throughput virtual screening and ADME properties prediction - Maxim Y. Gvozdev; Iveta S. Turomsha; Viktoryia V. Savich; Yaroslav V. Faletrov; Anastasiya V. Sidarenka; Vladimir M. Shkumatov; Natalia V. Loginova (Archives of Microbiology, 2024)

Size matters: Aerobic methane oxidation in sediments of shallow thermokarst lakes - Rinat Manasypov; Lichao Fan; Artem G. Lim; Ivan V. Krickov; Oleg S. Pokrovsky; Yakov Kuzyakov; Maxim Dorodnikov (Global Change Biology, 2024)
Shallow thermokarst lakes are important sources of greenhouse gases (GHGs) such as methane (CH 4 ) and carbon dioxide (CO 2 ) resulting from continuous permafrost thawing due to global warming. Concentrations of GHGs dissolved in water typically increase with decreasing lake size due to coastal abrasion and organic matter delivery. We hypothesized that (i) CH 4 oxidation depends on the natural oxygenation gradient in the lake water and sediments and increases with lake size because of stronger wind‐induced water mixing; (ii) CO 2 production increases with decreasing lake size, following the dissolved organic matter gradient; and (iii) both processes are more intensive in the upper than deeper sediments due to the in situ gradients of oxygen (O 2 ) and bioavailable carbon. We estimated aerobic CH 4 oxidation potentials and CO 2 production based on the injection of 13 C‐labeled CH 4 in the 0–10 cm and 10–20 cm sediment depths of small (~300 m 2 ), medium (~3000 m 2 ), and large (~10 6 m 2 ) shallow thermokarst lakes in the West Siberian Lowland. The CO 2 production was 1.4–3.5 times stronger in the upper sediments than in the 10–20 cm depth and increased from large (158 ± 18 nmol CO 2 g −1 sediment d.w. h −1 ) to medium and small (192 ± 17 nmol CO 2 g −1 h −1 ) lakes. Methane oxidation in the upper sediments was similar in all lakes, while at depth, large lakes had 14‐ and 74‐fold faster oxidation rates (5.1 ± 0.5 nmol CH 4 ‐derived CO 2 g −1 h −1 ) than small and medium lakes, respectively. This was attributed to the higher O 2 concentration in large lakes due to the more intense wind‐induced water turbulence and mixing than in smaller lakes. From a global perspective, the CH 4 oxidation potential confirms the key role of thermokarst lakes as an important hotspot for GHG emissions, which increase with the decreasing lake size.

Selective hydrodesulfurization of FCC naphtha over carbon coated alumina supported CoMoS catalysts - Mariya A. Kazakova; Anna A. Salomatina; Vasily Yu. Pereyma; Igor P. Prosvirin; Arcady V. Ishchenko; Oleg V. Klimov; Aleksandr S. Noskov; Maxim O. Kazakov (Fuel, 2023)

Submicron polymer particles loaded with piperine: Preparation from fucoidan and evaluation of morphology, release profile, and antioxidant activity - Emmanuel O. Mensah; Emmanuella T. Bulya; Artem S. Minin; Maxim A. Mironov (Food Hydrocolloids, 2023)

Cell-cycle arrest and mitochondria-dependent apoptosis induction in T-47D cells by the capsular polysaccharide from the marine bacterium Kangiella japonica KMM 3897 - Alexandra S. Kuzmich; Lyudmila A. Romanenko; Maxim S. Kokoulin (Carbohydrate Polymers, 2023)

Towards electronic smelling of ketones and alcohols at sub- and low ppms by pinky-sized on-chip sensor array with SnO2 mesoporous layer gradually engineered by near IR-laser - Maksim A. Solomatin; Marko Radovic; Alexander A. Petrunin; Demid A. Kirilenko; Alexey S. Varezhnikov; Georges Dubourg; Mikhail Yu. Vasilkov; Alexey M. Bainyashev; Andrea Nesterovic; Ilia Kiselev; Konstantin B. Kostin; Yuri P. Martynyuk; et al. (Chemical Engineering Journal, 2023)

Application of the Ugi reaction for preparation of submicron capsules based on sugar beet pectin - Rita S. Alqubelat; Manar M. Obiedallah; Artem S. Minin; Giuseppe Lazzara; Maxim A. Mironov (Molecular Diversity, 2023)

Transport of the Tumen River water to the Far Eastern Marine Reserve (Posyet Bay) based on in situ, satellite data and Lagrangian modeling using ROMS current velocity output - Pavel A. Fayman; Pavel A. Salyuk; Maxim V. Budyansky; Alexandr V. Burenin; Aleksandr A. Didov; Nadezhda A. Lipinskaya; Vladimir I. Ponomarev; Aleksandr A. Udalov; Yuri N. Morgunov; Michael Yu. Uleysky; Sergey S. Shkramada; Mikhail K. Pichugin (Marine Pollution Bulletin, 2023)

Impact of manganese accumulation on Na,K-ATPase expression and function in the cerebellum and striatum of C57Bl/6 mice - Larisa V. Smolyaninova; Yulia A. Timoshina; Daniil S. Berezhnoy; Tatiana N. Fedorova; Ivan V. Mikheev; Irina F. Seregina; Nadezhda A. Loginova; Maxim G. Dobretsov (NeuroToxicology, 2023)

Combining USY and ZSM-23 in Pt/zeolite hydrocracking catalyst to produce diesel and lube base oil with improved cold flow properties - Maxim O. Kazakov; Marina Yu. Smirnova; Maxim E. Dubinin; Tatyana S. Bogomolova; Pavel P. Dik; Ivan S. Golubev; Mikhail E. Revyakin; Oleg V. Klimov; Aleksandr S. Noskov (Fuel, 2023)

Catalytic aerobic desulfurization of fuels in the presence of nanosized mixed carbide FeWC - Argam V. Akopyan; Ekaterina A. Eseva; Raman A. Mnatsakanyan; David A. Davtyan; Maxim O. Lukashov; Ivan S. Levin; Alexey A. Sadovnikov; Alexander V. Anisimov; Anna M. Terzyan; Artur M. Agoyan; Eduard Karakhanov (Chemical Engineering Journal, 2023)

Structural characterization and physicochemical properties of the exopolysaccharide produced by the moderately halophilic bacterium Chromohalobacter salexigens, strain 3EQS1 - Ibrahim M. Ibrahim; Yuliya P. Fedonenko; Elena N. Sigida; Maxim S. Kokoulin; Vyacheslav S. Grinev; Ivan G. Mokrushin; Gennady L. Burygin; Andrey M. Zakharevich; Alexander A. Shirokov; Svetlana A. Konnova (Extremophiles, 2023)

Pan-cancer antagonistic inhibition pattern of ATM-driven G2/M checkpoint pathway vs other DNA repair pathways - Marianna A. Zolotovskaia; Alexander A. Modestov; Maria V. Suntsova; Anastasia A. Rachkova; Elena V. Koroleva; Elena V. Poddubskaya; Marina I. Sekacheva; Victor S. Tkachev; Andrew V. Garazha; Alexander A. Glusker; Aleksander P. Seryakov; Uliana S. Vladimirova; et al. (DNA Repair, 2023)

Large-scale bioproduction of natural astaxanthin in Yarrowia lipolytica - Evgeniya Y. Yuzbasheva; Maria O. Taratynova; Iuliia M. Fedyaeva; Dmitry A. Dementev; Vladimir S. Korobov; Alexander S. Fedorov; Lara Sellés Vidal; Tigran V. Yuzbashev; Sergey P. Sineoky; Maxim Mikheev (Bioresource Technology Reports, 2023)

Degradation of micro-nano-sized polytetrafluoroethylene and acrylic fluorinated copolymer particles in the periwinkle digestive tract - Vyacheslav S. Odintsov; Alexander A. Karpenko; Maxim A. Karpenko (Environmental Science and Pollution Research, 2022)

Visualization and quantification of carbon “rusty sink” by rice root iron plaque: Mechanisms, functions, and global implications - Liang Wei; Zhenke Zhu; Bahar S. Razavi; Mouliang Xiao; Maxim Dorodnikov; Lichao Fan; Hongzhao Yuan; Andrey Yurtaev; Yu Luo; Weiguo Cheng; Yakov Kuzyakov; Jinshui Wu; et al. (Global Change Biology, 2022)
Paddies contain 78% higher organic carbon (C) stocks than adjacent upland soils, and iron (Fe) plaque formation on rice roots is one of the mechanisms that traps C. The process sequence, extent and global relevance of this C stabilization mechanism under oxic/anoxic conditions remains unclear. We quantified and localized the contribution of Fe plaque to organic matter stabilization in a microoxic area (rice rhizosphere) and evaluated roles of this C trap for global C sequestration in paddy soils. Visualization and localization of pH by imaging with planar optodes, enzyme activities by zymography, and root exudation by 14 C imaging, as well as upscale modeling enabled linkage of three groups of rhizosphere processes that are responsible for C stabilization from the micro‐ (root) to the macro‐ (ecosystem) levels. The 14 C activity in soil (reflecting stabilization of rhizodeposits) with Fe 2+ addition was 1.4–1.5 times higher than that in the control and phosphate addition soils. Perfect co‐localization of the hotspots of β‐glucosidase activity (by zymography) with root exudation ( 14 C) showed that labile C and high enzyme activities were localized within Fe plaques. Fe 2+ addition to soil and its microbial oxidation to Fe 3+ by radial oxygen release from rice roots increased Fe plaque (Fe 3+ ) formation by 1.7–2.5 times. The C amounts trapped by Fe plaque increased by 1.1 times after Fe 2+ addition. Therefore, Fe plaque formed from amorphous and complex Fe (oxyhydr)oxides on the root surface act as a “rusty sink” for organic matter. Considering the area of coverage of paddy soils globally, upscaling by model revealed the radial oxygen loss from roots and bacterial Fe oxidation may trap up to 130 Mg C in Fe plaques per rice season. This represents an important annual surplus of new and stable C to the existing C pool under long‐term rice cropping.

Synthesis of 8-phenyl substituted 3-benzazecines with allene moiety, their thermal rearrangement and evaluation as acetylcholinesterase inhibitors - Maxim S. Kobzev; Alexander A. Titov; Elena V. Alexandrova; Rosa Purgatorio; Marco Catto; Elena A. Sorokina; Tatiana N. Borisova; Alexey V. Varlamov; Cosimo D. Altomare; Leonid G. Voskressensky (Molecular Diversity, 2022)

Interceptor potential of C60 fullerene aqueous solution: a comparative analysis using the example of the antitumor antibiotic mitoxantrone - Victoria A. Salo; Anatoly S. Buchelnikov; Maxim P. Evstigneev (European Biophysics Journal, 2022)

Quasi-Permanent Mushroom-like Dipole in the Lofoten Basin - Vladimir S. Travkin; Tatyana V. Belonenko; Maxim V. Budyansky; Sergey V. Prants; Michael Yu. Uleysky; Vladimir G. Gnevyshev; Roshin P. Raj (Pure and Applied Geophysics, 2022)

Computer simulation of merotelic kinetochore-microtubule attachments: corona size is more important than other cell parameters - Maxim A. Krivov; Fazoil I. Ataullakhanov; Pavel S. Ivanov (Chromosome Research, 2021)

Palynological study of Asian Thismia (Thismiaceae: Dioscoreales) reveals an unusual pollen type - Elena E. Severova; Svetlana V. Polevova; Sophia V. Yudina; Ba Vuong Truong; Thi Xuyen Do; Sahut Chantanaorrapint; Kenji Suetsugu; Shuichiro Tagane; Xing Guo; Mikhail I. Schelkunov; Maxim S. Nuraliev (Plant Systematics and Evolution, 2021)

The San Diego Nathan Shock Center: tackling the heterogeneity of aging - Gerald S. Shadel; Peter D. Adams; W. Travis Berggren; Jolene K. Diedrich; Kenneth E. Diffenderfer; Fred H. Gage; Nasun Hah; Malene Hansen; Martin W. Hetzer; Anthony J. A. Molina; Uri Manor; Kurt Marek; et al. (GeroScience, 2021)

In situ X-ray diffraction study of chrysotile at high P–T conditions: transformation to the 3.65 Å phase - Sergey V. Goryainov; John S. Tse; Serge Desgreniers; Saori I. Kawaguchi; Yuanming Pan; Anna Yu. Likhacheva; Maxim S. Molokeev (Physics and Chemistry of Minerals, 2021)

Size compartmentalization of energy channeling in terrestrial belowground food webs - Anton M. Potapov; Oksana L. Rozanova; Eugenia E. Semenina; Vladislav D. Leonov; Olga I. Belyakova; Varvara Yu. Bogatyreva; Maxim I. Degtyarev; Anton S. Esaulov; Anastasiya Yu. Korotkevich; Alexey A. Kudrin; Elena A. Malysheva; Yuri A. Mazei; et al. (Ecology, 2021)
Size‐structured food webs form integrated trophic systems where energy is channeled from small to large consumers. Empirical evidence suggests that size structure prevails in aquatic ecosystems, whereas in terrestrial food webs trophic position is largely independent of body size. Compartmentalization of energy channeling according to size classes of consumers was suggested as a mechanism that underpins functioning and stability of terrestrial food webs including those belowground, but their structure has not been empirically assessed across the whole size spectrum. Here we used stable isotope analysis and metabolic regressions to describe size structure and energy use in eight belowground communities with consumers spanning 12 orders of magnitude in living body mass, from protists to earthworms. We showed a negative correlation between trophic position and body mass in invertebrate communities and a remarkable nonlinearity in community metabolism and trophic positions across all size classes. Specifically, we found that the correlation between body mass and trophic level is positive in the small‐sized (protists, nematodes, arthropods below 1 μg in body mass), neutral in the medium‐sized (arthropods of 1 μg to 1 mg), and negative in the large‐sized consumers (large arthropods, earthworms), suggesting that these groups form compartments with different trophic organization. Based on this pattern, we propose a concept of belowground food webs being composed of (1) size‐structured micro‐food web driving fast energy channeling and nutrient release, for example in microbial loop; (2) arthropod macro‐food web with no clear correlation between body size and trophic level, hosting soil arthropod diversity and subsidizing aboveground predators; and (3) “trophic whales,” sequestering energy in their large bodies and restricting its propagation to higher trophic levels in belowground food webs. The three size compartments are based on a similar set of basal resources, but contribute to different ecosystem‐level functions and respond differently to variations in climate, soil characteristics and land use. We suggest that the widely used vision of resource‐based energy channeling in belowground food webs can be complemented with size‐based energy channeling, where ecosystem multifunctionality, biodiversity, and stability are supported by a balance across individual size compartments.

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Freshwater Mollusca of the Circumpolar Arctic: a review on their taxonomy, diversity and biogeography - Maxim V. Vinarski; Ivan N. Bolotov; Olga V. Aksenova; Eugeniy S. Babushkin; Yulia V. Bespalaya; Alexander A. Makhrov; Ivan O. Nekhaev; Ilya V. Vikhrev (Hydrobiologia, 2021)

A Role for Extracellular Vesicles in SARS-CoV-2 Therapeutics and Prevention - Jatin Machhi; Farah Shahjin; Srijanee Das; Milankumar Patel; Mai Mohamed Abdelmoaty; Jacob D. Cohen; Preet Amol Singh; Ashish Baldi; Neha Bajwa; Raj Kumar; Lalit K. Vora; Tapan A. Patel; et al. (Journal of Neuroimmune Pharmacology, 2021)

Textile-based cyanobacteria biocomposites for potential environmental remediation applications - Rachel Hart; Pichaya In-na; Maxim V. Kapralov; Jonathan G.M. Lee; Gary S. Caldwell (Journal of Applied Phycology, 2021)
Microalgae and cyanobacteria are effective platforms for environmental remediation (phycoremediation), particularly of air and water. There is limited scope to deploy suspension cultures due to space, cost and maintenance challenges—driving an imperative towards biofilm-based treatment systems; however, these systems are ill-equipped for rapid and mobile deployment. In this study we explored the main technical challenges to developing cheap, accessible and low-maintenance engineered biofilm systems (biocomposites) comprising cyanobacteria ( Synechococcus elongatus ) immobilised to a range of textiles ( n = 4) by natural or synthetic latex binders ( n = 16), chitosan or shellac. Biocomposite viability (measured as net CO 2 uptake) was assessed over 20 days in semi-batch trials. No maintenance was required during this period as the humidity within the reactor was sufficient to support metabolism. Two commercial natural latex binders (AURO 320 and 321) supported strong growth within the biocomposite, outperforming suspension controls. There was variation in textiles performance, with an 80/20 polyester-cotton blend performing most consistently. Biocomposite formulation was varied in terms of binder solids content and cell loading rate, with 5% solids and 2.5% cell loading the most effective combination. We demonstrate the technical feasibility of fabricating functional textile-based cyanobacteria biocomposites and discuss this within the context of developing decentralised wastewater treatment services.

Forest Structural Complexity and Biomass Predict First-Year Carbon Cycling Responses to Disturbance - Christopher M. Gough; Jeff W. Atkins; Ben Bond-Lamberty; Elizabeth A. Agee; Kalyn R. Dorheim; Robert T. Fahey; Maxim S. Grigri; Lisa T. Haber; Kayla C. Mathes; Stephanie C. Pennington; Alexey N. Shiklomanov; Jason M. Tallant (Ecosystems, 2021)

Multi‐site generalized dissimilarity modelling reveals drivers of species turnover in ectoparasite assemblages of small mammals across the northern and central Palaearctic - Boris R. Krasnov; Georgy I. Shenbrot; Maxim M. Vinarski; Natalia P. Korallo‐Vinarskaya; Irina S. Khokhlova (Global Ecology and Biogeography, 2020)
Aim We studied compositional turnover in two ectoparasite taxa asking whether (a) the main driver of turnover (environmental factors, host composition, or distance) is the same in both taxa; (b) the turnover of rare and widespread fleas and mites is driven by different factors; and (c) the turnover of either fleas or mites or both respond to the same environmental gradients as the turnover of their hosts. Location Northern and central Palaearctic. Time period 1959–2004. Main taxa studied Fleas, gamasid mites, mammals. Methods We used data on fleas and mites collected from 30 and 20 regions, respectively, and applied a novel metric, zeta diversity, and a novel approach, multi‐site generalized dissimilarity modelling (MS‐GDM). Results In fleas, variance explained by the models with host turnover as a predictor was higher than that of models with environment and distance or environment only. In mites, similar proportions of variance were explained by models with and without a host‐associated predictor. Host turnover strongly affected the compositional turnover of fleas, whereas mite turnover was equally influenced by host turnover and dissimilarity in air temperature. When host turnover was removed from the models, temperature became the most important predictor of turnover, followed by precipitation (for both taxa) and distance (for fleas). The effects of host turnover and environment were stronger for turnover of rare than widespread species. Temperature was the most important predictor of the host turnover independently of whether distance was included in the model. Main conclusions We conclude that the strength and manifestation of the effects of host compositional turnover as compared to environmental dissimilarity differ between ectoparasite taxa. Moreover, the application of MS‐GDM allowed us to reveal patterns that were obscured or distorted in earlier studies.

Latitudinal decline in stand biomass and productivity at the elevational treeline in the Ural mountains despite a common thermal growth limit - Frank Hagedorn; Melissa A. Dawes; Maxim O. Bubnov; Nadezhda M. Devi; Andrey A. Grigoriev; Valeriy S. Mazepa; Zufar Y. Nagimov; Stepan G. Shiyatov; Pavel A. Moiseev (Journal of Biogeography, 2020)
Aim To quantify tree biomass and stand productivity of treeline ecotones and identify driving factors. Location treeline ecotones of seven regions from the South to Polar Urals, spanning a latitudinal gradient of 1,500 km. Taxa Picea obovata , Betula pubescens , Larix sibirica. Methods Stand biomass and productivity were estimated across 18 elevational transects from the tree species line to the closed forest line based on allometric measurements of 326 trees (including roots for 53 trees), stand structure assessments and demographic patterns of 20,600 trees. Stand growth data were linked to (a) temperatures monitored in situ for five years in the South and Polar Urals, (b) climate variables extrapolated from nearby climate stations and (c) measures of nutrient availability in soils and tree foliage. Results treeline position along the latitudinal gradient occurred at a similar mean growing season temperature. Despite the common cold limitation of tree distribution along the Ural mountain range, stand biomass and productivity within the treeline ecotone decreased by a factor of three and five from the South to the Polar Urals, mainly due to a declining stand density. Among climatic variables, growing season length decreased by 20% and winter temperatures declined by 4°C towards the Polar Urals, whereas growing degree days > 5°C remained similar, averaging 554 ± 9°C. Soil development was poorer in the Polar than in the South Urals, and plant‐available N and P in the soil were 20 and 30 times lower, respectively, probably due to lower winter temperatures. Main conclusions Our results suggest that once the thermal limitation for tree growth is relieved, soil fertility—restricted by permafrost and low soil temperatures during winter—plays a key and yet underexplored role for stand productivity in treeline ecotones. The observed latitudinal decline in stand productivity is important for above‐ and belowground diversity and functioning.

Patterns of zeta diversity in ectoparasite communities harboured by small mammals at three hierarchical scales: taxon-invariance and scale-dependence - Boris R. Krasnov; Maxim V. Vinarski; Natalia P. Korallo-Vinarskaya; Irina S. Khokhlova (Oecologia, 2020)

Colymbosaurines from the Upper Jurassic of European Russia and their implication for palaeobiogeography of marine reptiles - Maxim S. Arkhangelsky; Nikolay G. Zverkov; Mikhail A. Rogov; Ilya M. Stenshin; Evgeniya M. Baykina (Palaeobiodiversity and Palaeoenvironments, 2020)

Efficiency of updating the ionospheric models using total electron content at mid- and sub-auroral latitudes - Daria S. Kotova; Vladimir B. Ovodenko; Yury V. Yasyukevich; Maxim V. Klimenko; Konstantin G. Ratovsky; Anna A. Mylnikova; Elena S. Andreeva; Alexander E. Kozlovsky; Nina A. Korenkova; Ivan A. Nesterov; Yulia S. Tumanova (GPS Solutions, 2020)

Cationic penetrating antioxidants switch off Mn cluster of photosystem II in situ - Vasily V. Ptushenko; Alexei E. Solovchenko; Andrew Y. Bychkov; Olga B. Chivkunova; Andrey V. Golovin; Olga A. Gorelova; Tatiana T. Ismagulova; Leonid V. Kulik; Elena S. Lobakova; Alexandr A. Lukyanov; Rima I. Samoilova; Pavel N. Scherbakov; et al. (Photosynthesis Research, 2019)

The Impact of Bacillus subtilis KATMIRA1933 Supplementation on Telomere Length and Mitochondrial DNA Damage of Laying Hens - Maxim S. Makarenko; Vladimir A. Chistyakov; Alexander V. Usatov; Maria S. Mazanko; Evgeniya V. Prazdnova; Anzhelika B. Bren; Ivan F. Gorlov; Zoya B. Komarova; Michael L. Chikindas (Probiotics and Antimicrobial Proteins, 2019)

Staphylococcus aureus heme and siderophore-iron acquisition pathways - Brigid S. Conroy; Jason C. Grigg; Maxim Kolesnikov; L. Daniela Morales; Michael E. P. Murphy (BioMetals, 2019)

Scale-dependence in geographic variation in a freshwater gastropod across the Palearctic - Maxim V. Vinarski; Sergei S. Kramarenko (Molluscan Research, 2019)

Analysis of the motion of vacuolar volutin granules in Saccharomyces cerevisiae - Maxim S. Kharchuk; Andrey N. Glushenkov; Elena N. Gromozova (Folia Microbiologica, 2019)

Effects of JUN and NFE2L2 knockdown on oxidative status and NFE2L2/AP-1 targets expression in HeLa cells in basal conditions and upon sub-lethal hydrogen peroxide treatment - Anna A. Belanova; Victor K. Chmykhalo; Maxim S. Makarenko; Olga V. Lyangasova; Maria M. Belousova; Anzhela A. Aleksandrova; Peter V. Zolotukhin (Molecular Biology Reports, 2019)

Body size distribution in flea communities harboured by Siberian small mammals as affected by host species, host sex and scale: scale matters the most - Elena N. Surkova; Natalia P. Korallo-Vinarskaya; Maxim V. Vinarski; Luther van der Mescht; Elizabeth M. Warburton; Irina S. Khokhlova; Boris R. Krasnov (Evolutionary Ecology, 2018)

Staminate flower of Prunus s. l. (Rosaceae) from Eocene Rovno amber (Ukraine) - Dmitry D. Sokoloff; Michael S. Ignatov; Margarita V. Remizowa; Maxim S. Nuraliev; Vladimir Blagoderov; Amin Garbout; Evgeny E. Perkovsky (Journal of Plant Research, 2018)

Allele-Specific Biased Expression of the CNTN6 Gene in iPS Cell-Derived Neurons from a Patient with Intellectual Disability and 3p26.3 Microduplication Involving the CNTN6 Gene - Maria M. Gridina; Natalia M. Matveeva; Veniamin S. Fishman; Aleksei G. Menzorov; Helen A. Kizilova; Nikolay A. Beregovoy; Igor I. Kovrigin; Inna E. Pristyazhnyuk; Igor P. Oscorbin; Maxim L. Filipenko; Anna A. Kashevarova; Nikolay A. Skryabin; et al. (Molecular Neurobiology, 2018)

Bacillus Probiotic Supplementations Improve Laying Performance, Egg Quality, Hatching of Laying Hens, and Sperm Quality of Roosters - Maria S. Mazanko; Ivan F. Gorlov; Evgeniya V. Prazdnova; Maxim S. Makarenko; Alexander V. Usatov; Anzhelika B. Bren; Vladimir A. Chistyakov; Alexey V. Tutelyan; Zoya B. Komarova; Natalia I. Mosolova; Denis N. Pilipenko; Olga E. Krotova; et al. (Probiotics and Antimicrobial Proteins, 2018)

Temperature gradient affects differentiation of gene expression and SNP allele frequencies in the dominant Lake Baikal zooplankton species - Larry L. Bowman; Elizaveta S. Kondrateva; Maxim A. Timofeyev; Lev Y. Yampolsky (Molecular Ecology, 2018)
Local adaptation and phenotypic plasticity are main mechanisms of organisms’ resilience in changing environments. Both are affected by gene flow and are expected to be weak in zooplankton populations inhabiting large continuous water bodies and strongly affected by currents. Lake Baikal, the deepest and one of the coldest lakes on Earth, experienced epilimnion temperature increase during the last 100 years, exposing Baikal's zooplankton to novel selective pressures. We obtained a partial transcriptome of Epischura baikalensis (Copepoda: Calanoida), the dominant component of Baikal's zooplankton, and estimated SNP allele frequencies and transcript abundances in samples from regions of Baikal that differ in multiyear average surface temperatures. The strongest signal in both SNP and transcript abundance differentiation is the SW ‐ NE gradient along the 600+ km long axis of the lake, suggesting isolation by distance. SNP differentiation is stronger for nonsynonymous than synonymous SNP s and is paralleled by differential survival during a laboratory exposure to increased temperature, indicating directional selection operating on the temperature gradient. Transcript abundance, generally collinear with the SNP differentiation, shows samples from the warmest, less deep location clustering together with the southernmost samples. Differential expression is more frequent among transcripts orthologous to candidate thermal response genes previously identified in model arthropods, including genes encoding cytoskeleton proteins, heat‐shock proteins, proteases, enzymes of central energy metabolism, lipid and antioxidant pathways. We conclude that the pivotal endemic zooplankton species in Lake Baikal exists under temperature‐mediated selection and possesses both genetic variation and plasticity to respond to novel temperature‐related environmental pressures.

Iron: a Strong Element in the Pathogenesis of Chronic Hyperglycaemia After Acute Pancreatitis - Shayal K. Chand; Ruma G. Singh; Sayali A. Pendharkar; Maxim S. Petrov (Biological Trace Element Research, 2018)

Pro-inflammatory cytokines after an episode of acute pancreatitis: associations with fasting gut hormone profile - Sayali A. Pendharkar; Ruma G. Singh; Shayal K. Chand; Aya Cervantes; Maxim S. Petrov (Inflammation Research, 2018)

Crude oil at concentrations considered safe promotes rapid stress-response in Lake Baikal endemic amphipods - Ekaterina P. Shchapova; Denis V. Axenov-Gribanov; Yulia A. Lubyaga; Zhanna M. Shatilina; Kseniya P. Vereshchagina; Ekaterina V. Madyarova; Eugeniy S. Protasov; Maxim A. Timofeyev (Hydrobiologia, 2018)

The diversity and antibiotic properties of actinobacteria associated with endemic deepwater amphipods of Lake Baikal - Eugenii S. Protasov; Denis V. Axenov-Gribanov; Yuriy V. Rebets; Irina V. Voytsekhovskaya; Bogdan T. Tokovenko; Zhanna M. Shatilina; Andriy N. Luzhetskyy; Maxim A. Timofeyev (Antonie van Leeuwenhoek, 2017)

Partial structure and immunological properties of lipopolysaccharide from marine-derived Pseudomonas stutzeri KMM 226 - Maxim S. Kokoulin; Ekaterina V. Sokolova; Yuriy N. Elkin; Lyudmila A. Romanenko; Valery V. Mikhailov; Nadezhda A. Komandrova (Antonie van Leeuwenhoek, 2017)

Goldspotted spinefoot Siganus punctatus (Siganidae) age‐based reproductive life history and fisheries vulnerability - K. Rhodes; D. Hernandez‐Ortiz; M. Ioanis; W. Washington; S. Maxim; K. Olpet; S. Malakai (Journal of Fish Biology, 2017)
Between February 2015 and 2016, samples of the Indo‐Pacific goldspotted spinefoot Siganus punctatus were taken from local fish markets, feeding sites and nursery grounds on the main island of Pohnpei, Micronesia, to ascertain sexual pattern, reproductive seasonality, age, growth and mortality. Microscopic examinations of gonads identified two seasonal peaks in reproduction: February to May and September to December, with evidence of some spawning activity in most months. Ripe females were observed 4 days on either side of the new moon. Females first matured at c . 180 mm fork length ( L F ) and 1 year of age, which coincides with their entry into the fishery. Ninety five per cent of individuals were less than 3 years and the oldest fish were 8 years. To examine the species vulnerability to fishing, a tag‐and‐recapture study was conducted over 4 months in 2015 in a locally managed marine area and at an unprotected site. Findings suggest high residency and high vulnerability to fishing at shallow‐water feeding sites and restricted migration overall. The placement of marine protected areas within critical habitat appears to be an effective conservation strategy for this species, particularly when combined with gear and seasonal market restrictions during vulnerable life‐history phases.

Beta-diversity of ectoparasites at two spatial scales: nested hierarchy, geography and habitat type - Elizabeth M. Warburton; Luther van der Mescht; Michal Stanko; Maxim V. Vinarski; Natalia P. Korallo-Vinarskaya; Irina S. Khokhlova; Boris R. Krasnov (Oecologia, 2017)

Strobilanthes barbigera (Acanthaceae), a new species from Vietnam - John R. I. Wood; Maxim S. Nuraliev; Andrey N. Kuznetzov; Svetlana P. Kuznetzova; R. W. Scotland (Kew Bulletin, 2017)

Origin of a divergent mtDNA lineage of a freshwater snail species, Radix balthica, in Iceland: cryptic glacial refugia or a postglacial founder event? - Ivan N. Bolotov; Olga V. Aksenova; Yulia V. Bespalaya; Mikhail Y. Gofarov; Alexander V. Kondakov; Inga S. Paltser; Andri Stefansson; Oksana V. Travina; Maxim V. Vinarski (Hydrobiologia, 2017)

Antipsychotic inductors of brain hypothermia and torpor-like states: perspectives of application - Yury S. Tarahovsky; Irina S. Fadeeva; Natalia P. Komelina; Maxim O. Khrenov; Nadezhda M. Zakharova (Psychopharmacology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Actinobacteria possessing antimicrobial and antioxidant activities isolated from the pollen of scots pine (Pinus sylvestris) grown on the Baikal shore - Denis V. Axenov-Gribanov; Irina V. Voytsekhovskaya; Yuriy V. Rebets; Bogdan T. Tokovenko; Tatyana A. Penzina; Tatyana G. Gornostay; Renat V. Adelshin; Eugenii S. Protasov; Andriy N. Luzhetskyy; Maxim A. Timofeyev (Antonie van Leeuwenhoek, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

C60 fullerene affects elastic properties and osmoregulation reactions of human lymphocytes - Marina Yu. Skorkina; Evgenia A. Sladkova; Elena A. Shamray; Olga V. Cherkashina; Maxim P. Evstigneev; Anatoly S. Buchelnikov; Yuriy I. Prylutskyy; Uwe Ritter (European Biophysics Journal, 2015)

How does the discrepancies among taxonomists affect macroecological patterns? A case study of freshwater snails of Western Siberia - Maxim V. Vinarski; Sergei S. Kramarenko (Biodiversity and Conservation, 2015)

A permeability transition in liver mitochondria and liposomes induced by α,ω-dioic acids and Ca2+ - Mikhail V. Dubinin; Victor N. Samartsev; Maxim E. Astashev; Alexey S. Kazakov; Konstantin N. Belosludtsev (European Biophysics Journal, 2014)

Treeline advances along the Urals mountain range – driven by improved winter conditions? - Frank Hagedorn; Stepan G. Shiyatov; Valeriy S. Mazepa; Nadezhda M. Devi; Andrey A. Grigor'ev; Alexandr A. Bartysh; Valeriy V. Fomin; Denis S. Kapralov; Maxim Terent'ev; Harald Bugman; Andreas Rigling; Pavel A. Moiseev (Global Change Biology, 2014)
High‐altitude treelines are temperature‐limited vegetation boundaries, but little quantitative evidence exists about the impact of climate change on treelines in untouched areas of Russia. Here, we estimated how forest‐tundra ecotones have changed during the last century along the Ural mountains. In the South, North, Sub‐Polar, and Polar Urals, we compared 450 historical and recent photographs and determined the ages of 11 100 trees along 16 altitudinal gradients. In these four regions, boundaries of open and closed forests (crown covers above 20% and 40%) expanded upwards by 4 to 8 m in altitude per decade. Results strongly suggest that snow was an important driver for these forest advances: (i) Winter precipitation has increased substantially throughout the Urals (~7 mm decade −1 ), which corresponds to almost a doubling in the Polar Urals, while summer temperatures have only changed slightly (~0.05 °C decade −1 ). (ii) There was a positive correlation between canopy cover, snow height and soil temperatures, suggesting that an increasing canopy cover promotes snow accumulation and, hence, a more favorable microclimate. (iii) Tree age analysis showed that forest expansion mainly began around the year 1900 on concave wind‐sheltered slopes with thick snow covers, while it started in the 1950s and 1970s on slopes with shallower snow covers. (iv) During the 20th century, dominant growth forms of trees have changed from multistemmed trees, resulting from harsh winter conditions, to single‐stemmed trees. While 87%, 31%, and 93% of stems appearing before 1950 were from multistemmed trees in the South, North and Polar Urals, more than 95% of the younger trees had a single stem. Currently, there is a high density of seedlings and saplings in the forest‐tundra ecotone, indicating that forest expansion is ongoing and that alpine tundra vegetation will disappear from most mountains of the South and North Urals where treeline is already close to the highest peaks.

Dynamics of the exponential integrate-and-fire model with slow currents and adaptation - Victor J. Barranca; Daniel C. Johnson; Jennifer L. Moyher; Joshua P. Sauppe; Maxim S. Shkarayev; Gregor Kovačič; David Cai (Journal of Computational Neuroscience, 2014)

Insights into pathophysiology of dystropy through the analysis of gene networks: an example of bronchial asthma and tuberculosis - Elena Yu. Bragina; Evgeny S. Tiys; Maxim B. Freidin; Lada A. Koneva; Pavel S. Demenkov; Vladimir A. Ivanisenko; Nikolay A. Kolchanov; Valery P. Puzyrev (Immunogenetics, 2014)

Interceptor effect of C60 fullerene on the in vitro action of aromatic drug molecules - Galyna B. Skamrova; Ivan Laponogov; Anatoly S. Buchelnikov; Yuriy G. Shckorbatov; Svitlana V. Prylutska; Uwe Ritter; Yuriy I. Prylutskyy; Maxim P. Evstigneev (European Biophysics Journal, 2014)

Interaction of Phospholipase A of the E. coli Outer Membrane with the Inhibitors of Eucaryotic Phospholipases A2 and Their Effect on the Ca2+-Induced Permeabilization of the Bacterial Membrane - Konstantin N. Belosludtsev; Natalia V. Belosludtseva; Maxim S. Kondratyev; Alexey V. Agafonov; Yuriy A. Purtov (The Journal of Membrane Biology, 2014)

Mean shift-based clustering of remotely sensed data with agricultural and land-cover applications - Lior Friedman; Nathan S. Netanyahu; Maxim Shoshany (International Journal of Remote Sensing, 2013)

On the reliability of quantitation of biological effect in drug–interceptor–DNA systems - Anatoly S. Buchelnikov; Vladyslav P. Evstigneev; Leticia E. Rodríguez Oropeza; Maxim P. Evstigneev (European Biophysics Journal, 2013)

Breeding ecology of the globally threatened Sociable Lapwing Vanellus gregarius and the demographic drivers of recent declines - Rob D. Sheldon; Johannes Kamp; Maxim A. Koshkin; Ruslan S. Urazaliev; Timur K. Iskakov; Rob H. Field; Albert R. Salemgareev; Valery V. Khrokov; Vasily A. Zhuly; Sergey L. Sklyarenko; Paul F. Donald (Journal of Ornithology, 2013)

Male hosts drive infracommunity structure of ectoparasites - Boris R. Krasnov; Michal Stanko; Sonja Matthee; Anne Laudisoit; Herwig Leirs; Irina S. Khokhlova; Natalia P. Korallo-Vinarskaya; Maxim V. Vinarski; Serge Morand (Oecologia, 2011)

Development of adenoviral vector-based mucosal vaccine against influenza - Irina L. Tutykhina; Denis Y. Logunov; Dmitriy N. Shcherbinin; Maxim M. Shmarov; Amir I. Tukhvatulin; Boris S. Naroditsky; Alexander L. Gintsburg (Journal of Molecular Medicine, 2011)

Different natural organic matter isolates cause similar stress response patterns in the freshwater amphipod, Gammarus pulex - Darya S. Bedulina; Maxim A. Timofeyev; Martin Zimmer; Elke Zwirnmann; Ralph Menzel; Christian E. W. Steinberg (Environmental Science and Pollution Research, 2010)

Geographical patterns of abundance: testing expectations of the ‘abundance optimum’ model in two taxa of ectoparasitic arthropods - Boris R. Krasnov; Georgy I. Shenbrot; Irina S. Khokhlova; Maxim Vinarski; Natalia Korallo‐Vinarskaya; Robert Poulin (Journal of Biogeography, 2008)
Aim The ‘abundance optimum’ hypothesis predicts that species abundance peaks in the locality with the most favourable conditions and decreases with an increase of distance from that locality. We tested this prediction for 9 fleas and 13 gamasid mite species. Location We used published data on fleas and gamasid mites that are parasitic on small mammals throughout the Palaearctic. Methods For each ectoparasite, we computed the correlation between the relative abundance on its principal host species in a region and the distance from that region to the region of maximum abundance. Then, the correlation coefficients were used in a meta‐analysis. We also made a cross‐species comparison between relative abundances in localities (a) closest to and (b) furthest from the locality of maximum abundance. Results Although the relationship between the relative abundance in a region and the distance from that region to the region of maximum abundance was negative in 19 out of 22 ectoparasites, it was only statistically significant in three of them. However, a meta‐analysis of coefficients of correlations across all species revealed a significant negative effect of the distance from the region of maximum abundance on relative abundance in a particular region. A cross‐species comparison between relative abundances in the localities closest to and furthest from the locality of maximum abundance demonstrated that the former were significantly higher than the latter. Main conclusions A lack of strict host specificity in the ectoparasites studied, and the absence of any strong spatial correlations among the environmental variables affecting ectoparasite reproduction and abundance, may provide an explanation for the spatial independence in abundance values of most species. However, a preference for a particular host even in host‐opportunistic parasites combined with species‐specific environmental preferences could be the reason behind the weak, but significant, negative abundance–distance relationship across species. The contradiction between results obtained when separate species were considered and when the overall pattern was analysed across species suggests that there exists a general underlying spatial pattern that can often be masked by other factors.

Macro‐ to fine‐scale spatial and temporal distributions and dynamics of phytoplankton and their environmental driving forces in a small montane lake in southern California, USA - David A. Caron; Beth Stauffer; Stefanie Moorthi; Amarjeet Singh; Maxim Batalin; Eric A. Graham; Mark Hansen; William J. Kaiser; Jnaneshwar Das; Arvind Pereira; Amit Dhariwal; Bin Zhang; et al. (Limnology and Oceanography, 2008)
A wireless network of buoys, two autonomous robotic boats, and an autonomous tethered vertical profiling system were used to characterize phytoplankton dynamics and spatiotemporal changes in chemical and physical forcing factors in a small montane lake (Lake Fulmor, Idyllwild, California). Three deployments each year were conducted in 2005 and 2006 to examine seasonal changes in the structure of the lake and phytoplankton assemblage, as well as fine‐scale temporal and spatial variations. The buoys yielded fine‐scale temporal patterns of in situ fluorescence and temperature, while the vertical profiling system yielded two‐dimensional, cross‐sectional profiles of several parameters. The autonomous vehicles provided information on fluorescence and corresponding temperature patterns across the surface of the lake. Average, lake‐wide chlorophyll concentrations increased 10‐ fold seasonally, and strong anoxia developed in the hypolimnion during the summer. The latter process dramatically affected vertical chemical gradients in the 5 m water column of the lake. Small‐scale spatial (

Founder mutations in early-onset, familial and bilateral breast cancer patients from Russia - Anna P. Sokolenko; Maxim E. Rozanov; Natalia V. Mitiushkina; Natalia Yu. Sherina; Aglaya G. Iyevleva; Elena V. Chekmariova; Konstantin G. Buslov; Evgeny S. Shilov; Alexandr V. Togo; Elena M. Bit-Sava; Dmitry A. Voskresenskiy; Oleg L. Chagunava; et al. (Familial Cancer, 2007)

A novel three-component reaction designed by the combinatorial method: Heteroarenes, isothiocyanates and isocyanides - Maxim A. Mironov; Sergey S. Maltsev; Vladimir S. Mokrushin; Vasiliy A. Bakulev (Molecular Diversity, 2005)

Differential responses of human brain cells to West Nile virus infection - Maxim C-J Cheeran; Shuxian Hu; Wen S Sheng; Ayesha Rashid; Phillip K Peterson; James R Lokensgard (Journal of NeuroVirology, 2005)

Ugi reaction in aqueous solutions: A simple protocol for libraries production - Maxim A. Mironov; Maria N. Ivantsova; Vladimir S. Mokrushin (Molecular Diversity, 2003)

An Alu-mediated deletion at Xp11.23 leading to Wiskott-Aldrich syndrome - Maxim I. Lutskiy; Lauren N. Jones; Fred S. Rosen; Eileen Remold-O'Donnell (Human Genetics, 2002)

Photosynthesis and photoprotection in symbiotic corals - Maxim Y. Gorbunov; Zbigniew S. Kolber; Michael P. Lesser; Paul G. Falkowski (Limnology and Oceanography, 2001)
In zooxanthellate corals, excess excitation energy can be dissipated as heat (nonphotochemical quenching), thereby providing protection against oxidative damage by supraoptimal light in shallow reefs. To identify and quantify the photoprotective mechanisms, we studied the diel variability of chlorophyll fluorescence yields and photosynthetic parameters in situ in corals, using moored and SCUBA‐based fast‐repetition‐rate fluorometers. The results reveal that nonphotochemical quenching is triggered prior to saturation of photosynthetic electron transport by down‐regulation of the reaction centers of Photosystem II (PSII). This process dissipates up to 80% of the excitation energy. On a sunny day in shallow waters, the daily integrated flux of photons absorbed, and subsequently dissipated as heat, is ~4 times that used for photosynthesis. Fluorescence quenching is further accompanied by a slight reduction in the functional absorption cross section for PSII that results from thermal dissipation of excitation energy in the light‐harvesting antennae. These two processes are highly dynamic and adjust to irradiance changes on timescales consistent with the passage of clouds across the sky. Under supraoptimal irradiance, however, up to 30% of PSII reaction centers become photoinhibited, and these are repaired only after several hours of low irradiance. In shallow corals, between 10% and 20% of the reactions centers are chronically photoinhibited and appear to remain permanently nonfunctional throughout the year. Our results establish, for the first time, the suite of biophysical mechanisms that optimize photosynthesis while simultaneously providing photoprotection in symbiotic corals in situ.

Measurement of photosynthetic parameters in benthic organisms in situ using a SCUBA‐based fast repetition rate fluorometer - Maxim Y. Gorbunov; Paul G. Falkowski; Zbigniew S. Kolber (Limnology and Oceanography, 2000)
Benthic photoautotrophic organisms significantly contribute to the productivity of shallow tropical coastal ecosystems. However, measurements of photosynthetic light use and dissipation in benthic organisms are complicated by taxonomic diversity, spatial heterogeneity, natural variability in local nutrient, irradiance, and temperature regimes, as well as destructive sampling protocols. To help overcome these problems, we developed a SCUBA‐based fast repetition rate (FRR) fluorometer for measurements of variable chlorophyll fluorescence in corals, sea grasses, macroalgae, and algal turfs. Photosynthetic light use and electron transport can be readily calculated from variable fluorescence kinetics. Using the SCUBA‐based FRR fluorometer, changes in photosynthetic processes can be measured nondestructively in situ with high spatial and temporal resolution. Here we describe the instrument design and characteristics and present representative field results.

Measuring photosynthetic parameters in individual algal cells by Fast Repetition Rate fluorometry - Maxim Y. Gorbunov; Zbigniew S. Kolber; Paul G. Falkowski (Photosynthesis Research, 1999)